HUBUNGAN TERPAAN KAMPANYE EARTH HOUR INDONESIA DAN TINGKAT SELF EFFICACY TERHADAP PENERAPAN GAYA HIDUP HEMAT ENERGI - Rifqah Nailah; Yanuar Luqman; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Climate change is caused by high concentrations of greenhouse gases produced by humans from energy produced by burning fossil fuels as an energy source. High electricity consumption in Indonesia results in high greenhouse gas emissions. Therefore, efforts are needed from society to prevent the negative impacts of high levels of greenhouse gases such as climate change and rising earth temperatures. The Earth Hour campaign, as one of the pro-environment campaigns, promotes a lifestyle shift to energy saving as an effort to tackle climate change. The aim of the research is to see whether there is a positive relationship between exposure to the Earth Hour campaign and the adoption of an energy-saving lifestyle, based on the Theory of Reasoned Action. The second objective is to see whether there is a positive relationship between an individual's level of self-efficacy towards implementing an energy-saving lifestyle on the basis of Social Cognitive Theory. Research data was collected from 100 respondents who were exposed to the Earth Hour campaign, then the data was analyzed using the Kendall Tau_b correlation equation. The research results show that there is no relationship at all between exposure to the Earth Hour campaign and adopting an energy-saving lifestyle. On the other hand, the level of self-efficacy and the adoption of an energy-saving lifestyle have a very significant value so that there is a positive relationship with a correlation efficiency of 0.269. Based on the research results, it is recommended that parties interested in supporting the implementation of an energy-saving lifestyle can look for other supporting factors besides the Earth Hour campaign and the level of self-efficacy.